Loss Analysis of High Frequency Transformers on a 3kW-Class DC-DC Converter using the Co-Simulation of Circuit and electromagnetic field analysis - Park, Young-un; Oh, Seung-yeol; Park, Je-suk; Kim, Dae-kyong (International Journal of Engineering and Technology, 2018)
Background/Objectives: This study examined the loss analysis of a high frequency transformer using the thermal-electromagnetic coupled 3D-FEA considering practical converter circuit to improve the more accurate temperature analysis.Methods/Statistical analysis: The circuit used is a 3kW-class DC-DC converter. The circuit used was a 3kW-class DC-DC converter. FEA was used to analyze the electromagnetic field. The FEA modeling is based on the practical converter circuit and the measured current waveform.Findings: Thermal-electromagnetic coupled analysis was carried out to compare the results of the experiment and FEA models. The transformer flux density and thermal analysis of the stationary state was less than 0.38[T] and 35 [â„ƒ].Improvements/Applications: Most thermal studies for high frequency transformers are analytical and thermal equivalent circuit models. Therefore, thermal-electromagnetic coupled 3D-finite element analysis (FEA) considering the practical frequency excitations is required.Â Â